S100A4 targets PPP1CA/IL-17 to inhibit the senescence of sheep endometrial epithelial cells - Jiao, Xiyao; Jiao, Yaoxuan; Cui, Jingwen; Zhang, Haorui; Li, Xiangyun; Chu, Zhili; Wu, Xinglong (Frontiers in Veterinary Science, 2024)
BackgroundGonadotropin-releasing hormone (GnRH) is commonly used in animal reproduction and production, but it was previously reported that GnRH decreases the embryo implantation rate during artificial insemination or embryo transfer in sheep. In addition to the finding that GnRH can target S100A4 to inhibit endometrial epithelial cells proliferation, it was also found that endometrial cells were in poor condition and experienced cell death in S100A4 knockout mice, but the mechanism is unclear.MethodsThe protein PPP1CA, which interacts with S100A4, was detected by immunoprecipitation-mass spectrometry of overexpression and knockdown of S100A4 and PPP1CA. The effect of S100A4 and PPP1CA on cell senescence was detected by Galactosidase staining. To further reveal the mechanism effect of S100A4 and PPP1CA on cell senescence, transcriptome sequencing was conducted. Additionally, in vivo experiments were performed to assess PPP1CA protein expression in the endometrial tissue of S100A4 knockout mice.ResultsS100A4 inhibited cell senescence by activating PPP1CA, while PPP1CA overexpression suppressed the activation of the IL-17 signaling pathway. Inhibition of the IL-17 signaling pathway inhibited the senescence of endometrial cells.ConclusionS100A4 can target the PPP1CA/IL-17 signaling pathway and inhibit endometrial epithelial cell senescence.